Developmental YAPdeltaC determines adult pathology in a model of spinocerebellar ataxia type 1 - Kyota Fujita (Nature Portfolio, 2017)
Ataxin-1, linked to spinocerebellar ataxia type 1, is known to interact with the orphan nuclear receptor RORα. Here, Fujita and colleagues show that genetic supplementation of RORα-interacting protein YAPdeltaC during early development can rescue the adult pathologies of SCA1 mouse model.